Dissemination of the oil draining spinner on the small business of oyster mushroom chips in Meteseh Village, Semarang City - Purnomo, Purnomo; Sulistyaningsih, Dwi (Universitas Muhammadiyah Magelang, 2021)
The high oil content in fried products, including mushroom chips, can cause low quality chips. Chips contain a lot of oil which causes easy oxidation which can cause a rancid odor. This service aims to improve the quality of chips through the application of an oil draining spinner. The application of this machine is intended to reduce the maximum oil content in the oyster mushroom chips. The implementation stage begins with providing partners with a complete understanding of the tool. Furthermore, the engine performance test was carried out in the oil draining process, and the evaluation of the draining results is carried out. The results show that partners understand very well the parts, the function, and the working principle of the machine. Draining using the machine can effectively reduce the oil content of the chips, although a few chips were found to be damaged due to friction or impact with the machine wall. The draining capacity and resistance of the chips to not go rancid can be increased.